Oscillatory Structural Forces Across Dispersions of Micelles With Variable Surface Charge - Ludwig, Michael; Ritzert, Philipp; Geisler, Ramsia; Prévost, Sylvain; von Klitzing, Regine (Frontiers in Soft Matter, 2022)
When two surfaces interact across colloidal dispersions, oscillatory structural forces often arise due to an ordering of colloidal particles. Although this type of forces was intensively studied, the effect of the surface charge of the colloidal particles is still poorly understood. In the present study, the surface charge of colloidal particles is varied by changing the ratio of nonionic (Tween20) and anionic (sodium dodecyl sulfate, SDS) surfactants of micellar dispersions. The same micellar systems were previously characterised with small-angle neutron scattering (SANS) by the authors, revealing that mixed nonionic-anionic surfactant micelles with variable surface charge form. The present paper addresses the ordering phenomena of the micellar systems under confinement. Therefore, forces across these dispersions were measured for varying surface charges and volume fractions of the micelles, using colloidal-probe atomic force microscopy (CP-AFM). The combination of SANS and CP-AFM experiments allows the dispersions structure in bulk and under geometrical confinement to be compared in terms of the characteristic interparticle distance, correlation length, and ordering strength: In bulk and under confinement, the characteristic intermicellar distance increases by introducing surface charges to micelles until the electrostatic repulsion forces the micelles into a specific ordering. There, the characteristic intermicellar distance purely relates to the micelle volume fraction ϕ as ∝ ϕ^(−1/3). While in dispersions of uncharged micelles the characteristic intermicellar distance is reduced from bulk to confinement, no such compressibility is observed once the micelles are charged. Furthermore, variation of the micelles surface charge has only little effect on the correlation length of the micelles ordering which is mainly governed by hard-sphere interactions, especially in concentrated dispersions. Introducing surface charges, however, enhances the ordering strength (i.e. the amplitude) of oscillatory structural forces due to stronger electrostatic repulsions of the micelles with the equally charged confining surface. This surface-induced effect is not represented in bulk scattering experiments.